Help anyone, if helped by some: Understanding generalized reciprocity through the lens of interaction ritual chain theory - Wang, B.; Liu, Yukun; Qian, J.; Parker, Sharon (2023)
The phenomenon ‘help anyone, if helped by some’ is known as generalized reciprocity. Most research has considered generalized reciprocity from the perspective of social exchange theory, focusing on an obligated to process. In this study, we apply the interaction ritual chain (IRC) theory to theorize that individuals can pay it forward based on their previous emotional experiences. Specifically, we developed and examined a theoretical model to address why and when receiving social support could promote employees' helping others. In Study 1, a between-person three-wave time-lagged study of 627 employees, we found that emotional energy (EE) mediated the relationship between receiving social support at work and recipients' subsequent helping behaviours. In Study 2, a 10-day experience sampling study among 144 employees, we replicated the indirect effect of receiving social support on helping behaviour via EE at the within-person level. We also identified, consistent with IRC theory, a cross-level moderating effect of workplace status that differed depending on whom individuals received support from. Specifically, received supervisor support led to more EE for employees with higher workplace status than for those lower in status. With respect to received coworker support, the effect of support on EE was stronger for those lower in status than for those higher in status. Overall, our results shed light on the emotional experiences involved in workplace social interactions and suggested energized to as an alternative mechanism for interpreting generalized reciprocity beyond the obligated to process.